Prospects of FEV6 using as alternative indicator of respiratory function assessment - O. V. Myronenko; O. V. Fesenko; V. V. Dmytrychenko; K. V. Zhulay (Zaporožskij Medicinskij Žurnal)
The aim of the study was to establish a correlation between the changes of external respiratory function leading indicators in patients with COPD and the presence of a positive response to the bronchodilator over an extended period of observation and the value of the FEV6 index in assessment of bronchial obstruction reversibility.